Efeito de variáveis ambientais e alteração da vegetação na riqueza de endemismos e comunidades de aves na caatinga - Arruda, André Ribeiro de (2017)
Bird communities, both regionally and locally, are the result of historical events and also of current ecological processes. Environmental factors such as temperature, water availability and vegetation cover are co-responsible for the distribution of the taxa and the structure of the communities. This relationship is even stronger in the endemic species, because they present a long selective history that narrows relations with the environment of occurrence. In the Caatinga, there is the hypothesis that its endemic birds are linked to both traditionally dry areas and areas with historical influence of humid forests. There is also the hypothesis that the avifauna in the Caatinga, even associated with an ecosystem with relatively low plant density, tends to lose wealth, abundance and diversity with the reduction of the original vegetation. In that sense, the first chapter compiled the georeferenced records of 52 endemic bird taxa of the Caatinga and modeled their potential distributions with indicators of presence or absence. The sum of all the modeled images indicated gradients of concentration of bird endemics throughout the region. In order to understand which factors influence the concentrations of endemism, the values of wealth were crossed with 26 environmental variables, among which, seven formed a model with high explanatory potential in the prediction of endemism in the region. Individually, rainfall presented a negative relation with the richness, suggesting that the typical avifauna of this domain is specialized and highly selected, from the evolutionary point of view, to the constant water stress and typical drought periods of the annual cycle in the region. This potential physiological stress is apparently softened by preference for areas with mild temperatures. Altitude, in turn, is generally associated with higher precipitations and seems to contradict the positive relationship between wealth and altitude. However, the influence of altitude on the richness of endemism may reflect the biogeographic history of area formation and not directly physiological limitations. The second chapter also sought to understand effects of environmental variations on birds in the Caatinga, however, on a local scale. Comparing two areas in Cariri Paraibano, with different use histories and soil cover, we evaluated the effect of alterations of the vegetal structure on the communities of birds. During two rainy periods, the richness and abundance of birds in both areas were recorded and from these records functional and phylogenetic diversity tests were applied, as well as a phylogenetic analysis of main components to identify which species and functional traits most contribute to the Structuring of the two communities. In general, it was possible to verify that the richness of birds is superior in the less disturbed area, possibly linked to the hypothesis of greater heterogeneity of habitats. The species composition also differed, more ecologically demanding species are associated with the less disturbed area, while species with low requirement are associated with the disturbed area. Similar traits were also found in the most influential functional traits, so traits associated with open areas were more common in the more disturbed area while traces facing dense vegetation were more common in the reserve area.